Pembuatan Pupuk Kompos dari Kotoran Sapi di Desa Mekar Jaya - Yunandra Yunandra; Muhammad Aryo Armanda; Daniel Ginting Suka; Anwary Mahsa; Wahyu Pratama Pratama; Reztiana Reztiana; Dwitya Nurrahma; Ika Nadia Sari; Dhea Ananda; Anastasya Anastasya; Yunita Yunita (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
Cow dung waste often poses a significant problem, leading to environmental pollution in places like Mekar Jaya Village, Kampar Kiri Tengah District, Kampar Regency. This service aims to address this issue by utilizing cow dung waste, not only to prevent environmental pollution but also to provide an additional source of income for livestock farmers in Mekar Jaya Village. The method of implementing these activities involves both socialization and hands-on field practice in managing cow dung waste. The results of these community service activities through socialization have led to an increase in the community's awareness of the importance of processing cow dung waste into fertilizer, thereby mitigating environmental pollution. This initiative is followed by practical demonstrations on how to produce cow dung compost. The process of manufacturing organic fertilizer has yielded positive results, meeting the expectations of the project.